Pengaruh Perilaku Santri Terhadap Kondisi Sanitasi Lingkungan di Pondok Pesantren Al-Urwatul Wutsqo - Silvia Qodariyati; Naniek Ratni Juliardi AR (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Environmental sanitation problems occur not only in households but also in educational institutions, including Islamic boarding schools. The aim of the research was to determine the environmental sanitation conditions at Al-Urwatul Wutsqo Jombang Islamic Boarding School and the influence of students' behaviour on the environmental sanitation conditions there. Observation and interview methods were used to determine the environmental sanitation conditions at Al-Urwatul Wutsqo Jombang Islamic Boarding School. Meanwhile, research on students' behavioural variables, namely knowledge, attitudes and actions through the method of filling out questionnaires. Based on the research results, it shows that there are still several indicators of environmental sanitation conditions that do not meet the requirements of legalregulations, one of which is the condition of providing clean water that does not meet the requirements as a raw material for drinking water because it has a rather high TDS level, namely 628 mg/L. Then, the resultsof the data analysis test showed that students' knowledge did not have a significant positive relationship with environmental sanitation conditions, but students' attitudes and behaviours had a significant positive relationship with environmental sanitation conditions.